Development Of Digital Based Flash Card Media On Thematic Learning In Ibtidaiyah Madrasah - Kesumawati, Diah; Habib, Mustafa; Lubis, Renni Ramadhani; Novianti, Yusda (Institut Agama Islam Negeri Palopo, 2022)
This research is research and development. This study uses the Four D development model. The stages in the Four D development model are definition, design, development, and dissemination. However, in this study, the stages used were only up to the development stage. The subjects of this study were students of class II MIN 15 Langkat, totaling 24 people with details of 13 males and 11 females. The object of research is digital-based flashcard media. This study aims to develop digital-based flashcard media. The data collection instruments were interviews, observations, questionnaire validation, and student responses. From the results of the validation carried out by media experts, material experts, and linguists it was declared feasible.